1992
DOI: 10.1007/bf00685549
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolites of the antitumor agentd-limonene capable of inhibiting protein isoprenylation and cell growth

Abstract: Limonene has been shown to be an effective, nontoxic chemopreventive and chemotherapeutic agent in chemically induced rat mammary-cancer models. The present study characterized circulating metabolites of limonene in female rats and determined their effects on cell growth. Metabolism of limonene was analyzed in plasma extracts by gas chromatography. Rapid conversion of limonene to two major metabolites was detected. These metabolites comprised more than 80% of the circulating limonene-derived material at 1 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 16 publications
3
56
0
1
Order By: Relevance
“…D-limonene is listed in the code of federal regulation as GRAS for use as a flavouring agent and in food preservation (Sun, 2007). Furthermore, several biochemical activities such as antimicrobial (Chikhoune, Hazzit, Kerbouche, Baaliouamer, & Aissat, 2013;Settanni et al, 2012;van Vuuren & Viljoen, 2007), antioxidant (Roberto, Micucci, Sebastian, Graciela, & Anesini, 2010), chemo-preventive (Crowell, Lin, Vedejs, & Gould, 1992;Wattenberg & Coccia, 1991), anticarcinogen (Crowell & Gould, 1994), as well as antidiabetic proprieties (Murali, Karthikeyan, & Saravanan, 2012) have been reported for D-limonene. The p-cymene, a biological precursor of carvacrol, is a hydrophobic chemical that might cause swelling of the cytoplasmic membrane of microorganisms (Ultee, Bennink, & Moezelaar, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…D-limonene is listed in the code of federal regulation as GRAS for use as a flavouring agent and in food preservation (Sun, 2007). Furthermore, several biochemical activities such as antimicrobial (Chikhoune, Hazzit, Kerbouche, Baaliouamer, & Aissat, 2013;Settanni et al, 2012;van Vuuren & Viljoen, 2007), antioxidant (Roberto, Micucci, Sebastian, Graciela, & Anesini, 2010), chemo-preventive (Crowell, Lin, Vedejs, & Gould, 1992;Wattenberg & Coccia, 1991), anticarcinogen (Crowell & Gould, 1994), as well as antidiabetic proprieties (Murali, Karthikeyan, & Saravanan, 2012) have been reported for D-limonene. The p-cymene, a biological precursor of carvacrol, is a hydrophobic chemical that might cause swelling of the cytoplasmic membrane of microorganisms (Ultee, Bennink, & Moezelaar, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered to be an ingredient with relatively low toxicity. Upon oral administration, D-limonene is rapidly and almost completely absorbed from the gastrointestinal tract of both humans and animals 3,4 . Other studies have shown that D-limonene does not pose a mutagenic, carcinogenic, or nephrotoxic risk to humans.…”
Section: Introductionmentioning
confidence: 99%
“…First, the effectiveness of the essential oils in remedy of sepsis is probably due to pharmacokinetic properties and the disposition of the caraway monoterpenes in the body. Considering the physicochemical properties of the terpenes, such as lipophilicity and molecular mass and size, penetration into and permeation through the skin as well as subsequent systemic effects can be expected (Crowell et al, 1992;Phillips et al, 1995;Stott et al, 1998;Hongratanaworakit & Buchbauer, 2006). The presence of aromatic compound glucosides, alkyl glycosides, glucides, nucleoside, and flavonoids in hydroalcoholic fraction of caraway seeds (Matsumura et al, 2002) offer relatively poor bioavailability to this fraction.…”
Section: Discussionmentioning
confidence: 99%